Teaching and learning in environmental law pedagogy, methodology and best practice - Du Plessis, Anél; Fowler, Robert; Hamman, Evan; Warnock, Ceri; Kennedy, Amanda (Law teacher) (The IUCN Academy of Environmental Law series, 2023)
"This unique book focuses specifically on teaching and learning in environmental law, exploring innovative techniques, tools and technologies employed across the globe to teach this ever more important subject. Chapters identify particular challenges that environmental law poses for pedagogy, offering a mix of theory and practical guidance to legal scholars who are seeking to take up, or improve, their teaching of this subject. Providing an examination of teaching formats and methodologies that are both innovative and particularly adapted to the teaching of environmental law, contributions explore topics such as digital learning, joint teaching, flipped classrooms and scenario-based approaches, as well as discussing teacher-based, reflective, student-centred and research-based methods. The book also considers specific contexts for teaching environmental law such as specialized postgraduate programs, supervision methods for research students, teaching within non-law programs, and teaching online. Environmental law scholars at all levels of university instruction will find this book an invaluable opportunity to learn about new methods and approaches to teaching in this area. Its insights into legal teaching methodologies more broadly will also be of interest to legal academics in other areas of the law"--Provided by publisher.